1982
DOI: 10.1002/jnr.490080223
|View full text |Cite
|
Sign up to set email alerts
|

Target control of neuronal development during formation of the spinal reflex arc: An operant model

Abstract: The effects of target tissues on the neural centers of the developing spinal reflex arc of frog tadpoles have been integrated to form a model explaining the spatial and temporal interactions of neuron and target. Spinal cord responds to appropriate targets earlier than does sensory ganglion in tissue culture. Neuronal growth and survival responses to target tissues in vitro may explain the regulation of development in situ.Key words: nerve growth, neuron survival, neuron maturation, nerve-target, spinal arc IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Other than developmental stage dependency, there appeared to be no hinderance in neurite extension under the conditions of this culture system. The fact that the stage XI DRG produced the densest neuritic networks coincides with other findings from our laboratory (Pollack and Muhlach, 1982), indicating that, a t least on collagen, the DRG is most responsive to the presence of its target tissues, i.e., the limb or spinal cord, a t stage XI, a time when target Fig. 3.…”
Section: Discussionsupporting
confidence: 85%
“…Other than developmental stage dependency, there appeared to be no hinderance in neurite extension under the conditions of this culture system. The fact that the stage XI DRG produced the densest neuritic networks coincides with other findings from our laboratory (Pollack and Muhlach, 1982), indicating that, a t least on collagen, the DRG is most responsive to the presence of its target tissues, i.e., the limb or spinal cord, a t stage XI, a time when target Fig. 3.…”
Section: Discussionsupporting
confidence: 85%
“…We further propose that the neurite-cell contacts may play a trophic role for neuronal differentiation. The flat cells innervated by neuritic extensions may release factors in the microenvironment ; neurite-promoting factors have been described to derive from glial cells, fibroblasts, and target cells such as muscle cells Collins, 1978;Dribin and Barrett, 1982;Manthorpe et al, 1980;Monard, 1973;Newgreen, 1984;Noble et al, 1984;Pollack and Muhlach, 1982;Varon and Adler, 19811. A rare but impressive growth pattern was the following: a long neurite extension began from a large aggregate, making contact with a smaller cluster of cells and appeared to be ensheathed (or be in contact) with a chain of spindle shaped cells. The possibility that this structure represents Schwann cells ensheathing neurite (axon?)…”
Section: Discussionmentioning
confidence: 99%
“…Although the identities of the neurons in the explants are not known, Cohen and Weldon (1980) previously showed that when these explants were cocultured with Xenopus muscle cells, 70% of the contacts will induce the formation of ACh receptor clustering, a feature characteristic of motoneurons (Cohen and Weldon, 1980;Kidokoro et al, 1980). In explant cultures of larval Rana pipens spinal cord, neuritic outgrowth has been related to spinal motoneurons Pollack and Muhlach 1982). Furthermore, the specializations induced by the beads bear a striking resemblance to those seen at the NMJ.…”
Section: Discussionmentioning
confidence: 99%